2010
DOI: 10.1177/0890334410365067
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Breastfeeding Duration Among Connecticut Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Participants

Abstract: This retrospective study aimed to identify factors associated with breastfeeding duration among women enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) of Hartford, Connecticut. The authors included mothers whose children were younger than 5 years and had stopped breastfeeding (N = 155). Women who had planned their pregnancies were twice as likely as those who did not plan them to breastfeed for more than 6 months (odds ratio, 2.15; 95% confidence interval, 1.00–4.64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…The study results show that young mothers and unwanted pregnancies are strongly associated with shorter EB durations, which was also found by Haughton et al 24 while studying 155 children covered by a North American nutritional supplementation program (WIC Program).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…The study results show that young mothers and unwanted pregnancies are strongly associated with shorter EB durations, which was also found by Haughton et al 24 while studying 155 children covered by a North American nutritional supplementation program (WIC Program).…”
supporting
confidence: 68%
“…Faleiros' et al 17 review found that prenatal care efficiently allows greater access to information on the benefits of EB, preventing early weaning. On the other hand, Haughton et al 24 did not find association between the knowledge gained during pregnancy and breastfeeding success.…”
mentioning
confidence: 99%
“…16 -19 More than $3.6 billion in annual health care costs would be saved if breastfeeding increased to the rates endorsed by Healthy People 2020, and $13 billion would be potentially saved annually if 90% of mothers in the United States exclusively breastfed their children as recommended. 5 Younger, less educated, and single racial/ethnic-minority mothers in the United States and Puerto Rico are at risk for early weaning from breastfeeding, 2, 20 -22 perhaps related to breastfeeding-related technical issues (ie, latching issues and resulting sore nipples 23,24 ), psychosocial issues (ie, early introduction of formula milk, 18,21 perception that infants prefer formula milk, 25 desire to keep infants full longer, 26 return to work, 26,27 confidence in breastfeeding, 25,28,29 and social support 28,30 ), and economic issues (ie, distribution of free infant formula by the Special Supplemental Nutrition Program for Women, Infants, and Children [WIC] 18,23 ).…”
mentioning
confidence: 99%
“…Breast milk is ideal and complete food for an infant for initial few months [1]. It provides nutrients and also helps in building up the immune system of newborns [2].…”
Section: Introductionmentioning
confidence: 99%